2018
DOI: 10.1002/epi4.12222
|View full text |Cite
|
Sign up to set email alerts
|

Widespread abnormalities in white matter integrity and their relationship with duration of illness in temporal lobe epilepsy

Abstract: SummaryObjectiveElucidation of abnormal connections throughout the whole brain is necessary to understand temporal lobe epilepsy (TLE). We examined abnormalities in whole‐brain white matter integrity and their relationship with duration of illness in patients with TLE.MethodsThe subjects were 15 patients with TLE and 17 healthy controls. Mean duration of illness in the TLE group was 21.6 years. Tract‐based spatial statistics (TBSS) were used for diffusion tensor imaging (DTI) analysis. Four diffusion tensor me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Significant associations were present in (1) ipsilateral fornix and (2) contralateral cingulum gyrus of left-TLE patients. Similar associations were shown previously, with a whole brain TBSS analysis by (Tsuda et al, 2018) also showing significant associations between epilepsy duration and FA of the fornix in adult TLE patients after multiple comparisons correction. However contrary to our findings, analyses by (Concha et al, 2009;Kemmotsu et al, 2011;Liu et al, 2012;Chiang et al, 2016;Hatton et al, 2020) found no significant associations between epilepsy duration and FA of the fornix.…”
Section: Discussionsupporting
confidence: 89%
“…Significant associations were present in (1) ipsilateral fornix and (2) contralateral cingulum gyrus of left-TLE patients. Similar associations were shown previously, with a whole brain TBSS analysis by (Tsuda et al, 2018) also showing significant associations between epilepsy duration and FA of the fornix in adult TLE patients after multiple comparisons correction. However contrary to our findings, analyses by (Concha et al, 2009;Kemmotsu et al, 2011;Liu et al, 2012;Chiang et al, 2016;Hatton et al, 2020) found no significant associations between epilepsy duration and FA of the fornix.…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with our findings regarding right temporal lobe damage. Tsuda et al () found reduced FA and increased MD and RD in widespread white matter regions of patients with TLE and that these changes were related to the duration of illness. As recurrent epileptiform discharges change the structure and function of both the temporal lobe and the entire brain (Maccotta et al, ), we found that BEN was significantly increased not only in the right middle temporal gyrus but also in other regions, such as the superior and middle frontal gyri, middle occipital gyrus, insula, putamen, and posterior cerebellum of the left hemisphere; these findings may have resulted from damage caused by epileptic discharges from the right temporal lobe to these brain regions, resulting in increased BEN.…”
Section: Discussionmentioning
confidence: 98%
“…However, heterogeneity of pathology, disease duration, seizure frequency and severity, and age of disease onset may also lead to attenuated detection of changes in TLE. Further studies on more homogeneous groups are needed to control for these potential confounders 24,25 .…”
Section: Discussionmentioning
confidence: 99%